The role of VEGF in predicting progression-free survival (PFS) and overall survival (OS) for ovarian carcinoma patients - Moh Nailul Fahmi; Kurniawan, Patricia Alika (Published by Universitas Gadjah Mada, 2025)
Vascular endothelial growth factor (VEGF) plays a pivotal role in highly vascularized tumors such as ovarian cancer. It can be detected in serum and ascitic fluid. This study aimed to determine the difference between VEGF in the blood serum level and ascitic fluid in predicting progression-free survival (PFS) and overall survival (OS) in patients with ovarian cancer. A prospective cohort study was conducted between 2018 and 2021 at Dr Sardjito General Hospital, Yogyakarta, Indonesia. The study included patients who underwent primary surgery for epithelial ovarian cancer. VEGF levels in both serum and ascitic fluid were measured using the human cytokine magnetic 10-plex panel for Luminex (Invitrogen commercial kit), based on the enzyme-linkedimmunosorbent assay (ELISA). PFS and OS were monitored until the end of the study period. A total of 40 patients were enrolled, with a median follow-up duration of 24 mo. Among participants, 22 patients (55%) experienced disease progression, and 50% survived. The median VEGF levels in serum and ascitic fluid were 720 and 1925 pg/mL, respectively. Receiver operating characteristic (ROC) curve analyses of PFS and OS revealed that VEGF levels in ascitic fluid had better predictive value than serum VEGF levels. The area under the curve(AUC) of ascites vs serum was 0.646 vs 0.567, with sensitivity of 83.3% vs 100% for PFS, whereas the AUC of ascites vs serum was 0.565 vs 0.548, with sensitivity of 50.0% vs 93.8% for OS. However, no statistical significance was observed (p>0.05). In conclusion, both VEGF ascites and serum failed to predict PFS and OS in ovarian cancer patients.